Education of Social Intelligence and Environmental Talents Based on Material and Vital Values in Quran Translation Text - Markhamah, M; Sufanti, Main; Rahmawati, Laili Etika; Sabardila, Atiqa; Prihatin, Indah; Lukiana, Dian (Universitas Muhammadiyah Surakarta, 2021)
This study examined material and vital values in Quran translated text (Indonesian) containing the word langit (sky, heaven), namely: (1) analyzing the material value and its role in educating the talents of social intelligence, and (2) examining the vital value and its role in educating environmental intelligence talent. This research utilized desciptive qualitative approach. Data collection used observation and documentation techniques. Data analysis was carried out using referential identity method. The results of the analysis of material values are of two kinds: (1) invitation material values and (2) prohibition material values. The material value of invitation included invitations to: (a) act to protect oneself from danger, (a) ask forgiveness from Allah, (c) be pious. The material value of prohibition includes the prohibition of: (a) being stingy, (b) saying falsities about Allah, (c) breaking the limits of religion. Material values that educate social intelligence talents included: (a) being a generous human being, (b) behaving naturally, not extreme, (c) seeking and studying science, especially religious knowledge. The vital values found in the study included: (1) it is God who made the earth as an expanse and the sky as a roof, rains down, gives fruit and sustenance to humans, (2) all processes from raining water, growing trees, bearing fruit, to maturity were done by Allah, (3) Allah is All-Knowing. These vital values educate the talents of environmental intelligence: (1) sustenance is not solely due to human efforts, but also because of Allah, (2) humans are obliged to manage natural resources and all of their contents to meet the needs of all of Allah’s creatures, (3) human knowledge to manage it is part of Allah’s knowledge.